Spatial analysis of Macau scam cases in Perlis / Nur Syafiqah Mahazal - Mahazal, Nur Syafiqah (2023)
The rise of Macau scam cases in Perlis has become a significant concern for law enforcement agencies and policymakers. To effectively combat this type of fraud and allocate resources efficiently, it is essential to gain a comprehensive understanding of the spatial patterns and trends associated with Macau scam occurrences. This problem emphasizes the lack of comprehensive spatial analysis in previous studies, which limits the understanding of the geographic distribution and clustering of these scams. This study aims to contribute to the existing knowledge by employing spatial analysis techniques to achieve three primary objectives: (1) To identify the Macau scam cases occur in Perlis between 2015 until 2021. (2) To locate the hotspot area of Macau scam victims in Police between 2015 until 2021. (3) To analyse the trend of Macau scam crime cases in Perlis. By employing advanced spatial analysis methods such as hotspot analysis, kernel density estimation, and spatial autocorrelation, this research examines the clustering patterns and spatial dependence of Macau scam incidents. The identification of hotspot areas will provide valuable insights for law enforcement agencies to concentrate their efforts on specific regions that are most vulnerable to Macau scam activities. The study's findings show significant regional patterns and hotspots of Macau scam instances in Perlis. Hotspot analysis finds statistically significant high-risk locations, providing useful information to law enforcement authorities for preventative and detection initiatives. Several recommendations are made based on the research findings. These include increasing public awareness and education campaigns, improving law enforcement collaboration, and executing targeted intervention tactics in high-risk locations.